Corallana nodosa (Schioedte and Meinert, 1879) (Crustacea: Isopoda: Corallanidae), attacking freshwater fish at the Durian Tunggal Dam, Melaka, Malaysia - Muhamad Zudaidy Jaapar (2019)
In January 2005, some dying freshwater fish were reported in Durian Tunggal Dam, Melaka. An isopod was observed to cause the injuries, lesions on various parts of the fish body. The isopod attaches at the base of the fins, on the head and abdomen, under scales and in the gill cavity. In one severe case, haemorrhages were seen all over the body of the infected fish, leading to its death. This isopod is not host specific as it attaches to various species of freshwater fish such as black tilapia (Oreochromis mossambicus), red tilapia (Oreochromis niloticus hybrid), common carp (Cyprinus carpio) and the goldfish (Carrasius auratus). Light-microscopic examination identified the isopod as Corallana nodosa (Schioedte and Meinert, 1879). The key identification characters were based on sparse setae on the maxilliped, short and tiny maxilla and maxillules generally hooked or with one or two terminal spines. An attempt to establish the life cycle of this parasite was not successful after 28 trials in laboratory. The isopods could survive up to day five under laboratory conditions.